Model of the speculative path of economic development - Kalitine, Boris S. (Journal of the Belarusian State University. Economics, 2021)
The work examines the potential of an enterprise using the speculative path of economic development: when the decision to change the price is not directly related to the increased costs of production and sales of products. The analysis of the speculative path of economic development was obtained on the basis of constructing an economic model that allows expressing the manufacturer’s net revenue through the essential parameters of the market. The price and volume of sales of goods or services, the absolute value of the coefficient of price elasticity of demand, the inflation rate for the period under consideration, the coefficient of production costs were included to them. The strengths and weaknesses of economic actions in the context of the SMR have been identified, and the problem of choosing the best decision-making option for the head of the enterprise has been solved. This research results are illustrated graphically.
Keywords: sales volume; price; revenue; speculation coefficient